Concept of healing of recurrent shoulder dislocation() - D’Angelo, Donato (Rev Bras Ortop, 2014)
This paper presents the main surgical techniques applied in the treatment of anterior recurrent shoulder dislocation, aiming the achievement of the normality of articulate movements. This was obtained by combining distinct surgical procedures, which allowed the recovery of a complete functional capacity of the shoulder, without jeopardizing the normality of movement, something that has not been recorded in the case of the tense sutures of the surgical procedures of Putti-Platt, Bankart, Latarjet, Dickson-O’Dell and others. The careful review of the methods applied supports the conclusion that recurrent shoulder dislocation can be cured, since cure has been obtained in 97% of the treated cases. However, some degree of limitation in the shoulder movement has been observed in most of the treated cases. Our main goal was to achieve a complete shoulder functional recovery, by treating simultaneously all of the anatomical–pathological lesions, without considering the so-called essential lesions. The period of post-operatory immobilization only last for the healing of soft parts; this takes place in a position of neutral shoulder rotation, since the use of vascular bone graft eliminates the need for long time immobilization, due to the shoulder stabilization provided by rigid fixation of the coracoid at the glenoid edge, as in the Latarjet's technique. Our procedure, used since 1959, comprises the association of several techniques, which has permitted shoulder healing without movement limitation. That was because of the tension reduction in the sutures of the subescapularis, capsule, and coracobraquialis muscles.